2018
DOI: 10.1021/acs.jpcc.7b11863
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptide Crystals as Reverse Osmosis Membranes for Water Desalination: Atomistic Simulation

Abstract: An atomistic simulation study is reported to investigate the capability of dipeptide crystals as reverse osmosis (RO) membranes for water desalination. Eight dipeptides are considered, namely, Ala-Val (AV), Val-Ala (VA), Ala-Ile (AI), Ile-Ala (IA), Val-Ile (VI), Ile-Val (IV), Val-Val (VV), and Leu-Ser (LS). It is revealed that water flux is governed by both pore size and helicity. With a relatively larger pore size, AV, AI, VV, and LS exhibit a higher water flux than VA, IA, VI, and IV. Despite similar pore si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…Here, a hydrogen bond is counted only when the donor−acceptor distance is less than 3.5 Å and the hydrogen−donor−acceptor angle is less than 30°. 19,47 Our calculation of the average strength of hydrogen bonds in a perfect NPG crystal obtained 27.91 kJ/mol at 0 K, which is quantitatively consistent with the results of ∼25 kJ/mol computed using DFT. 41 Figure 7a depicts the average strength of intermolecular hydrogen bonds and the number of intermolecular hydrogen bonds per molecule (N HB ), which remain unchanged from 218.15 to 298.15 K. This result suggests that the orientations of NPG molecules in the crystal remain unchanged upon the temperature change.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Here, a hydrogen bond is counted only when the donor−acceptor distance is less than 3.5 Å and the hydrogen−donor−acceptor angle is less than 30°. 19,47 Our calculation of the average strength of hydrogen bonds in a perfect NPG crystal obtained 27.91 kJ/mol at 0 K, which is quantitatively consistent with the results of ∼25 kJ/mol computed using DFT. 41 Figure 7a depicts the average strength of intermolecular hydrogen bonds and the number of intermolecular hydrogen bonds per molecule (N HB ), which remain unchanged from 218.15 to 298.15 K. This result suggests that the orientations of NPG molecules in the crystal remain unchanged upon the temperature change.…”
Section: Resultssupporting
confidence: 84%
“…C is the energy conversion factor, r is the distance, and ε and δ are the parameters of Lennard-Jones potential. Here, a hydrogen bond is counted only when the donor–acceptor distance is less than 3.5 Å and the hydrogen–donor–acceptor angle is less than 30°. , Our calculation of the average strength of hydrogen bonds in a perfect NPG crystal obtained 27.91 kJ/mol at 0 K, which is quantitatively consistent with the results of ∼25 kJ/mol computed using DFT …”
Section: Resultssupporting
confidence: 82%
“…Peptide assemblies with channel diameters >4 Å (FF and LS) show similar antibacterial activity while the ones with narrow channels (<4 Å, IV and VI) are inactive. Zhao et al showed by atomistic simulation that IV and VI allow only relatively restricted transport of water molecules, much smaller than LS water flux [41]. FF was not investigated by the authors, but the crystal structure of this dipeptide shows that it assembles in water filled nanotubes [19].…”
Section: Discussionmentioning
confidence: 99%
“…FF was not investigated by the authors, but the crystal structure of this dipeptide shows that it assembles in water filled nanotubes [19]. LS possess high salt rejection (Na + and Cl − ) [41] which suggests that antimicrobial activity arises from a sudden increase in the membrane permeability to water. Thus, our results seem to be in agreement with the findings of Gazit and colleagues that dipeptide nanostructures may form pores in inner and outer bacterial membranes [6].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the previous studies [5,47,88,89], to speed up the converging of MD simulations, high pressure was used for water desalination. However, Cohen-Tanugi and Grossman [90] have verified the system's efficiency at low pressures.…”
Section: The Simulation Methodsmentioning
confidence: 99%